2015
DOI: 10.1097/aln.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Brain Serotonin Content Regulates the Manifestation of Tramadol-induced Seizures in Rats

Abstract: The authors determined that serotonin-reduced rats were predisposed to tramadol-induced seizures, and that serotonin concentrations were negatively associated with seizure thresholds. Moreover, serotonin receptor antagonism precipitated seizure manifestation, indicating that tramadol-induced seizures are distinct from serotonin syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…The modulatory role of the brain neurotransmitters in various models of epilepsy is already reported . In our study too, we found that 6‐Hz psychomotor seizures were accompanied by reduced brain levels of 5‐HT, DA, NE, histamine and GABA, and enhanced levels of Glu.…”
Section: Discussionsupporting
confidence: 79%
“…The modulatory role of the brain neurotransmitters in various models of epilepsy is already reported . In our study too, we found that 6‐Hz psychomotor seizures were accompanied by reduced brain levels of 5‐HT, DA, NE, histamine and GABA, and enhanced levels of Glu.…”
Section: Discussionsupporting
confidence: 79%
“…However, recent animal data strongly questioned their serotoninergic origin. Rat pretreatment with cyproheptadine, a serotonin receptor antagonist, did not abolish tramadol-induced seizures 4 while 5-hydroxytryptophane/benserazide, a combination enhancing brain serotonin concentration, was protective 5 or without effects on seizures. 4 These observations contrasted with the preventive effects of cyproheptadine on seizures induced by citalopram, a serotoninreuptake inhibitor, 6 suggesting that drug-related SS is a heterogeneous entity.…”
Section: To the Editormentioning
confidence: 93%
“…In contrast, the exact mechanisms of tramadol-induced seizures are still poorly understood. Based on animal data, seizures are unlikely to be related to serotoninergic mechanisms [19,20] and alternative pathways including GABAergic [21], histaminergic [22], and opioidergic [21] have been hypothesized, thus questioning the possible worsening role of naloxone in the treatment of tramadol overdose. Conformingly, in one observational study, naloxone administration was associated with increased probability of tracheal intubation [11].…”
Section: Introductionmentioning
confidence: 99%